Lung adenocarcinoma with EGFR 19Del and an ALK rearrangement benefits from alectinib instead of an EGFR-TKI: A case report. Issue 35 (2nd September 2022) - Wang, Hongbiao; Zhu, Sujuan; Li, Zhifeng; Qi, Xiaofang; Zhang, Liwen; Ke, Leiyu; Lin, Yingcheng
Abstract : Rationale: A remarkable concurrence of an EGFR mutation and an EML4-ALK fusion (double positive) occasionally occurs within a narrow number of patients. Previous studies using targeted therapy on EGFR/ALK co-mutated patients have commonly focused on single tyrosine kinase inhibitors (TKIs) or on the sequential use of EGFR -TKIs and ALK -TKIs. At present, no consensus exists regarding the treatment of patients with double positive mutations. The effectiveness of precision therapy also remains unknown. Patient concerns: A 53-year-old female non-smoker who described recurrent coughing and blood in her sputum over a month-long interval was examined at a local hospital. Diagnosis: Using computed tomography (CT) and positron emission tomography CT (PET-CT), the patient was diagnosed with Stage IVb lung adenocarcinoma (T4N3M1). Interventions: The patient had a novel ALK-RAB10 rearrangement identified using DNA sequencing, which, at the transcript level, was actually a canonical ALK fusion that caused a response to alectinib therapy. Outcomes: The patient has achieved partial remission (PR), with a progression free survival (PFS) of 16 months, and continues to benefit. Lessons: Our results may indicate differential sensitivities to TKIs in patients harboring an EGFR mutation and an ALK rearrangement. Our patient's response to alectinib, instead of to EGFR -TKIs, may lead to an expanded list of alectinib beneficiaries who have rare gene co-alterations in lung adenocarcinoma.